ROS-Responsive Biomimetic Nanocomplexes of Liposomes and Macrophage-Derived Exosomes for Combination Breast Cancer Therapy - Xu M; Bai L; Sun M; Yan X; Xiong Y; Wang Y; Guo Y; Liu X; Yu L; Zhong X; Ran M; Wang B; et al. (International Journal of Nanomedicine)
Minhao Xu,1,* Lu Bai,1,* Meng Sun,1 Xinlei Yan,1 Ying Xiong,2 Yu Wang,1 Yue Guo,1 Xingyou Liu,1 Leijie Yu,1 Xing Zhong,1 Mengqiong Ran,1 Ben Wang,3 Yaqin Tang,1 Robert J Lee,4 Jing Xie1 1School of Pharmacy and Bioengineering, Chongqing University of Technology, Chongqing, 400054, People’s Republic of China; 2Enrollment and Employment Department, Alumni-Office, Chongqing University of Technology, Chongqing, 400054, People’s Republic of China; 3Chengcheng County Hospital, Weinan, 715200, People’s Republic of China; 4College of Pharmacy, The Ohio State University, Columbus, OH, 43210-1291, USA*These authors contributed equally to this workCorrespondence: Jing Xie, Chongqing University of Technology, 69 hongguang Road, Chongqing, 400054, People’s Republic of China, Email xiejing33@cqut.edu.cnPurpose: Breast cancer is the most diagnosed cancer in women globally and it poses a major threat to women’s lives and health. As an essential therapeutic approach for breast cancer, chemotherapy encounters various clinical challenges like multidrug resistance and systemic toxicity. Nanotechnology has shown progress in addressing chemotherapy drug limitations. However, externally introduced nanoparticles are typically captured by the mononuclear phagocyte system (MPS) post-administration. To mitigate chemotherapy drug toxicity and enhance drug delivery efficiency, we combined ROS-responsive cationic liposomes (cLip) with macrophage-derived exosomes to create biomimetic nanocomplex (E-cLip-DTX/si) for co-delivery docetaxel (DTX) and Bcl-2 siRNA.Methods: We encapsulated docetaxel (DTX) and Bcl-2 siRNA as model drugs into biomimetic nanocomplexes and validated their antitumor efficacy in vitro and in vivo.Results: In vitro and vivo tests show that E-cLip-DTX/si can react to ROS, promote apoptosis of tumor cells effectively, and prolong circulation time. In breast cancer mouse model, E-cLip-DTX/si displays notable tumor accumulation efficiency, remarkable anti-tumor effects, and a favorable safety profile.Conclusion: We have developed a ROS-responsive biomimetic nanocomplexes that efficiently delivers DTX and Bcl-2 siRNA into the tumor site, overcoming the MPS barrier and extending the blood circulation time of the drug. Hence, biomimetic nanocomplex is a promising drug delivery platform with controlled drug release and biocompatibility for effective anti-tumor treatment. Keywords: co-delivery, RNAi, biomimetic delivery, combination therapy